Nutritional Status and Energy Intake of Adolescents in Umuahia Urban, Nigeria - Ogechi, Ukegbu Patricia; Akhakhia, Onimawo Ignatius; Ugwunna, Ukegbu Andrew (Pakistan Journal of Nutrition, 2007)
The purpose of this study was to provide information on anthropometry, body composition and energy intake of adolescents South Eastern Nigeria. The participants were 190 apparently healthy adolescent boys and girls aged 15-18 years with equal sex distribution. Participants were subjected to anthropometric measurements viz: height, weight, arm circumference and skinfold thickness. Energy intake was determined from individual weighed inventory for three consecutive days including a week-end day; part of the food sample was subjected to chemical analysis. According to the results, all measurements except BMI and arm circumference had significant differences (p